Common and Distinctive Functions of the Hippo Effectors Taz and Yap in Skeletal Muscle Stem Cell Function. (27th June 2017) - Sun, Congshan; De Mello, Vanessa; Mohamed, Abdalla; Ortuste Quiroga, Huascar P.; Garcia-Munoz, Amaya; Al Bloshi, Abdullah; Tremblay, Annie M.; von Kriegsheim, Alexander; Collie-Duguid, Elaina; Vargesson, Neil; Matallanas, David; Wackerhage, Henning; et al.
Abstract : Hippo pathway downstream effectors Yap and Taz play key roles in cell proliferation and regeneration, regulating gene expression especially via Tead transcription factors. To investigate their role in skeletal muscle stem cells, we analyzed Taz in vivo and ex vivo in comparison with Yap. Small interfering RNA knockdown or retroviral-mediated expression of wild-type human or constitutively active TAZ mutants in satellite cells showed that TAZ promoted proliferation, a function shared with YAP. However, at later stages of myogenesis, TAZ also enhanced myogenic differentiation of myoblasts, whereas YAP inhibits such differentiation. Functionally, while muscle growth was mildly affected in Taz (gene Wwtr1 –/– ) knockout mice, there were no overt effects on regeneration. Conversely, conditional knockout of Yap in satellite cells of Pax7 Cre-ERT2/+ : Yap fl ° x/fl ° x :Rosa26 Lacz mice produced a regeneration deficit. To identify potential mechanisms, microarray analysis showed many common TAZ/YAP target genes, but TAZ also regulates some genes independently of YAP, including myogenic genes such as Pax7, Myf5, and Myod1 (ArrayExpress–E-MTAB-5395). Proteomic analysis revealed many novel binding partners of TAZ/YAP in myogenic cells, but TAZ also interacts with proteins distinct from YAP that are often involved in myogenesis and aspects of cytoskeleton organization (ProteomeXchange–PXD005751). Neither TAZ nor YAP bind members of the Wnt destruction complex but both regulated expression of Wnt and Wnt-cross talking genes with known roles in myogenesis. Finally, TAZ operates through Tead4 to enhance myogenic differentiation. In summary, Taz and Yap have overlapping functions in promoting myoblast proliferation but Taz then switches to enhance myogenic differentiation.